Transcriptional Variability Associated With CRISPR-Mediated Gene Replacements at the Phytophthora sojae Avr1b-1 Locus - Gu, Biao; Shao, Guangda; Gao, Wenxin; Miao, Jianqiang; Wang, Qinhu; Liu, Xili; Tyler, Brett M. (Frontiers in Microbiology, 2021)
Transcriptional plasticity enables oomycetes to rapidly adapt to environmental challenges including emerging host resistance. For example, the soybean pathogen Phytophthora sojae can overcome resistance conferred by the host resistance gene Rps1b through natural silencing of its corresponding effector gene, Avr1b-1. With the Phytophthora CRISPR/Cas9 genome editing system, it is possible to generate site-specific knock-out (KO) and knock-in (KI) mutants, and investigate biological functions of target genes. In this study, the Avr1b-1 gene was deleted from the P. sojae genome using a homology-directed recombination strategy that replaced Avr1b-1 with a gene encoding the fluorescent protein mCherry. As expected, all selected KO transformants gained virulence on Rps1b plants, while infection of plants lacking Rps1b was not compromised. When a sgRNA resistant version of Avr1b-1 was re-introduced into the Avr1b-1 locus of an Avr1b KO transformant, KI transformants with a well-transcribed Avr1b-1 gene were unable to infect Rps1b-containing soybeans. However, loss of expression of the incoming Avr1b-1 gene was frequently observed in KI transformants, which resulted in these transformants readily infecting Rps1b soybeans. Similar variability in the expression levels of the incoming gene was observed with AVI- or mCherry-tagged Avr1b-1 constructs. Our results suggest that Avr1b-1 may be unusually susceptible to transcriptional variation.